2008
DOI: 10.1007/s11055-008-0045-8
|View full text |Cite
|
Sign up to set email alerts
|

Syncytial coupling of neurons in tissue culture and early ontogenesis

Abstract: Computerized time-lapse video recording was used to detect the process of formation of syncytial couplings between the processes of different neurons in dissociated neuron cultures. These studies showed that once the processes of one neuron had formed connections with another neuron, death of the cell body (its trophic center) was not followed by Wallerian degeneration. Translocation of cytoplasmic varicosities along the branches of one neuron to another was observed over periods of several hours. Electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…Perforations and fusions of filopodia have been shown in growth cones (Spooner et al, 1974). Syncytial connections between axons and dendrites have been found in large cerebral hemispheres in normal conditions (Santander et al, 1988) and in pathology (Samosudova et al, 2007) as well as in the intramural autonomic nervous system (Sotnikov et al, 2006, 2008). Earlier, the syncytial connection and fusion of nerve processes were identified in giant axons of cephalopod molluscs, crustaceans and polychaetes (Young, 1938; Nicol, 1948).…”
Section: Introductionmentioning
confidence: 99%
“…Perforations and fusions of filopodia have been shown in growth cones (Spooner et al, 1974). Syncytial connections between axons and dendrites have been found in large cerebral hemispheres in normal conditions (Santander et al, 1988) and in pathology (Samosudova et al, 2007) as well as in the intramural autonomic nervous system (Sotnikov et al, 2006, 2008). Earlier, the syncytial connection and fusion of nerve processes were identified in giant axons of cephalopod molluscs, crustaceans and polychaetes (Young, 1938; Nicol, 1948).…”
Section: Introductionmentioning
confidence: 99%
“…В лаборатории профессора О.С. Сотникова на протяжении многих лет подробно изучали механизм слияния нейронов посредством образования синцитиальной связи, приводящий к появлению многоядерных клеток [56]. Не исключено, что подобные слияния нейронов происходят с целью осуществления репаративных процессов при возникновении неблагоприятных условий.…”
Section: анеуплоидия и полиплоидия в головном мозге при старении и боunclassified
“…For example, the giant axons of the squid are generated by complete fusion of multiple neurons (third order giant fibers) and the syncytial axon is enclosed in a single sheath cell 27 . In vertebrates, some studies using electron microscopy and brightfield microscopy have reported the formation of neuronal syncytia in vitro and in vivo [28][29][30][31][32] ; unfortunately, however, these results were not quantified, making it difficult to determine their general relevance. Overall, the vast majority of neuronal cell-cell fusion events in different species have been described in the context of specific conditions or insults, which include viral infection, axonal injury, or the presence of stem or precursor cells ( Figure 5.2 and Table 5.1).…”
Section: Neuronal Cell-cell Fusion and Its Implicationsmentioning
confidence: 99%
“…Recruitment of EFF-1 to fusion sites in larval hypodermal cells was shown to be mediated at least in part by the actin regulator ), but other pathways may also exist. Much has been characterized about the molecular cascades that are activated in regenerating axons [28][29][30] and it is plausible that some of these molecules play a currently uncharacterized role in EFF-1 recruitment. …”
mentioning
confidence: 99%
See 1 more Smart Citation